RANCANG BANGUN MESIN PENGUPAS BUAH PINANG - Firkian Rinanda; Mgarifina N Ngarifin; Muhammad Yunus; Erwanto Erwanto (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Areca nut peeler machine is a machine that serves to separate the betel nut seeds from the coir. This machine is used by the community to process their agricultural products, and helps small entrepreneurs to produce large production, saving time and labor. Basically, the working principle of the areca nut peeler machine is the separation process between areca nut and areca nut seeds that occurs due to the rotation of the driving motor which is forwarded to the pulley and belt so that it moves the carrier shaft (screw) and the stripping cutting blade. The stripping is done by inserting the betel nut into the storage container. This research focuses on how to design and make a betel nut peeler machine using the basic product/machine design, so that the machine is able to peel betel nut according to the specified target.